CAR-based cell therapy: evaluation with bibliometrics and patent analysis - Yajun Yuan; Qihan Fu; Yaqun Zhang; Danhai Xu; Yeqing Wu; Qiufei Qiu; Wuyuan Zhou (Human Vaccines & Immunotherapeutics, 2021)
Chimeric antigen receptors-based cell therapies have shown impressive preclinical and clinical success and revolutionized biomedicine. However, the link between science and invention, the impact of international cooperation, and the influence and prestige of CARs research have not been explored. This study analyzed the landscape of peer-reviewed articles and patents related to CARs. A total of 5,681 publications were analyzed using bibliometrics and machine learning-based text mining to assess publication metrics, subject areas, and research hotspots. 5,010 Inpadoc families were also analyzed for patent filing trends, priority countries, and applicant and inventor rankings. The results show that CARs research has the following distinctive features: high research prestige among research community; strong global geographical bias in both academic output and patenting patterns; strong links between science and invention, but significant differences among countries; and an inverse relationship between country size and international collaboration rates.